Hubungan pengetahuan dan supervisi dengan penerapan prinsip enam benar dalam pemberian obat oleh perawat pelaksana - Nopan, Nopan Saputra; Sari, Yance Komela; Desnita, Eka (Sahabat Publikasi Kuu, 2022)
Nurses as part of the health care system is responsible for the provision of safe drugs. In order to achieve safe administration, nurses should pay attention to the six principles of client really is true, right drug, right dose, right time, right route, and right documentation. The phenomenon of the field obtained 30% of the drugs that are given are not documented, 15% of the drug is administered in a way that is not right, 23% of the drug is given at a wrong time, 2% of drugs are not given, 12% of the drug is administered at a dose yag right. Factors that affect the application of the principle of six true in drug delivery including knowledge and supervision. The aim of research to determine the relationship of knowledge and supervision with the correct application of the six principles of drug administration by nurses in inpatient unit RSI Siti Rahmah Padang. This type of research is analytic survey design using cross sectional study. The population around the nurses in the inpatient unit of 52 people, with a sampling technique using total sampling. Processing the data through the editing stage, coding, entry, and cleaning. Results were analyzed using univariate and bivariate chi square test with 95% confidence level α = 0.05. Based on the results, the application of the principle of six true in poor drug delivery (51.9%), while good (48.1%), 53.8% lower nurse's knowledge, while the less well supervised as much as 53.8%. There is a significant relationship between knowledge (p = 0.000) and supervision (0.027) with the correct application of the six principles in drug delivery.To perform an increase in drug administration services, health services should provide training and refresher on the principle of six correct drug administration. This can be done by organizing seminars / symposia and training regarding the professionalism of the administration of drugs and increase overall service.